PENGARUH TERAPI INHALASI UAP HANGAT DENGAN MINYAK KAYU PUTIH TERHADAP FREKUENSI NAPAS PADA ANAK BRONKOPNEUMONIA - Anggraeni, Reni; Ira Faridasari (Rena Cipta Mandiri, 2025)
Bronchopneumonia is one of the leading causes of morbidity in children and is often characterized by an increased respiratory rate due to airway disturbances. The management of bronchopneumonia requires not only pharmacological interventions but also non-pharmacological approaches. This study aims to determine the effect of warm steam inhalation therapy with eucalyptus oil on respiratory rate in children. A quantitative method was employed using a quasi-experimental design with a pretest-posttest control group approach. The population consisted of 25 children diagnosed with bronchopneumonia. A sample of 10 children was selected using accidental sampling and divided into two groups: an intervention group and a control group. The results showed a significant decrease in respiratory rate following the warm steam inhalation therapy with eucalyptus oil. Before therapy, most participants had a respiratory rate of ≥ 40 breaths per minute. After one day of therapy, the majority experienced a reduction in respiratory rate to within the normal range for their age group. Statistical analysis yielded a p-value < 0.05, indicating a significant difference before and after the intervention.